The Use of Temperate Tannin Containing Forage Legumes to Improve Sustainability in Forage–Livestock Production - Sebastian P. Lagrange (MDPI AG, 2021)
Greenhouse gas emissions from ruminant livestock production systems contribute significantly to the environmental footprint of agriculture. Emissions are lower for feedlot systems than for grass-based systems primarily because of the extra time required for grass-finished cattle to reach slaughter weight. In contrast, legume forages are of greater quality than grasses, which enhances intake and food conversion efficiencies, leading to improvements in production and reductions in environmental impacts compared with forage grasses. In addition, the presence of certain bioactives in legumes such as condensed tannins (CT) enhance the efficiency of energy and protein use in ruminants relative to grasses and other feeds and forages. Grazing tannin-containing legumes also reduce the incidence of bloat and improve meat quality. Synergies among nutrients and bioactives when animals graze diverse legume pastures have the potential to enhance these benefits. Thus, a diversity of legumes in feeding systems may lead to more economically, environmentally, and socially sustainable beef production than grass monocultures or feedlot rations.